Upgrading of Rakan Muda Activity Centre branch Batu Pahat for Rakan Muda at JKR 458.Jalan Kelab, Bandar Penggaram,83000 Batu Pahat,Johor / Aisyah Atika Mahdi - Mahdi, Aisyah Atika (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Architecture is a menisfestation of the student’s knowledge on all aspect an interior design that has been learned from the basic to the final presentation on the design proposal. The project that have been chosen for the final project is upgrading of Rakan Muda Activity Centre Branch Batu Pahat At JKR 458, Jalan Kelab, Bandar Penggaram, 83000 Batu Pahat, Johor. The purpose of upgrading this project is to attract teenagers. Besides, the target for upgrading this project is to upgrade the image and identity of the centre in order to promote Rakan Muda programmes and also to arrange the flow system at the interior in the building space. Apart from the concept and image that has been chosen to suit with the interior of the site, the student also need to research about the centre, the environment, the customers, the existing space in the building and also the client needs. At the same time this is to attract the teenagers with the concept that have been chosen and the image must suitable with the concept. Before getting a desired design that is suitable with the client, the arrengement of the space need to relate with the concept and solve the problems in Oder to achieve the objective of the design. So, the research that have been done need to fullfill the errangements of the project.